Game Edukasi: Apakah membuat belajar lebih menarik? - Pratama, Loviga Denny; Lestari, Wahyu; Bahauddin, Ahmad (At- Ta'lim : Jurnal Pendidikan, 2019)
Era Industri 4.0 has prompted academics to be able to apply a technology in a learning. However, this condition is still not supported by the availability of learning media used in schools. Therefore, this study aims to describe the response of academics, to educational game in learning. Two hundred twenty one students and fifty-three teachers from Probolinggo were randomly allocated to be the subject of this study. The responses collected with non-test techniques, were analyzed quantitatively and qualitatively. The results indicated educational game gain a positive response and greatly needed by academics. Furthermore, this result can be followed up for media developers and researchers to test the educational game in learning.